Assessing the determinants of tourism demand in greater mekong sub-region (gms) countries - Thien, Fung Thai (Universiti Malaysia Sarawak (UNIMAS), 2014)
Most countries in South-East Asia, especially Cambodia, Laos, Myanmar, Thailand, and Vietnam, have relatively undisturbed natural environment and their own unique as well as genuine culture. Such advantages have made travelling to these five countries more attractive for foreign visitors. This study empirically examines the tourism demand for these GMS countries from macroeconomic perspective. The panel data analysis was applied to examine the influence of income, tourism price, travel cost and global financial crisis towards tourism demand in these countries. Specifically, the static linear panel models have been used to estimate tourism demand model for GMS countries. Overall, the results indicate that income, tourism price and travel cost have significant influence on tourism demand in these countries. In order to attract more tourist arrival into these countries, the tourism facilities, promotions as well as attractions should be the focal of development for these countries. Such development is important as tourism sector has become an important contributor to the economy of GMS countries.